PARTISIPASI REMAJA DALAM KEGIATAN KEAGAMAAN DI MASJID BAITURRAHMAN PERUMAHAN BUMI KARAWANG PERMAI (Analisis Faktor dan Dampaknya) - Ady Nugroho; Oyoh Bariah; Afiyatun Kholifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze adolescent participation in religious activities at Baiturrahman Mosque, Bumi Karawang Permai Housing Complex, and to identify the influencing factors and impacts arising from such involvement. The research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving mosque administrators, adolescents, and members of the surrounding community. The findings indicate that adolescent participation in religious activities is reflected through their involvement in Islamic studies, social religious programs, Islamic holiday commemorations, and various mosque youth activities. The level of participation is influenced by several factors, including family support, peer environment, the role of mosque administrators, personal motivation, as well as the development of technology and social media. In addition, communicative approaches and inclusive activity environments play an important role in attracting adolescents to become actively involved in mosque activities. This participation has positive impacts on the development of religious character, the enhancement of social responsibility, and the strengthening of relationships among adolescents and the wider community. However, several obstacles remain, such as inconsistent attendance and the influence of digital activities that reduce the intensity of adolescent engagement. Therefore, sustainable guidance and development strategies are needed to encourage more active and productive adolescent participation in religious activities within the mosque environment.